A framework for the connectivity of an Internet of things - Corujo, Daniel
The evolution of telecommunications has allowed the coupling of networking features to an ever-increasing plethora of devices, enabling their connectivity and berthing of an Internet of Things (IoT). However, the assorted nature of such “things” implies disparate specifications, requirements and interfacing, for interaction with high-level decision modules, services and agents involved in the most distinct kind of scenarios. The joint operation of all networkable things in a truly integrated IoT vision requires a flexible framework able to facilitate interfacing with different elements and concepts. In this paper we present a framework that builds over the concept of Media Independence, further enhancing it to encompass the abstraction of different “things”, by providing the means for accessing their different interfacing procedures. We highlight the feasibility and flexibility of this framework by introducing it into an IoT scenario, enabling a flexible way for interface retrieval and control of different entities, paving the way for a truly universal and dynamic connectivity vision.